The contractor - Saleh, Tarik; Davis, J. P. (Actor); Iwanyk, Basil; Lee, Erica (Producer); Pine, Chris, 1980-; Jacobs, Gillian, 1982-; Foster, Ben, 1980-; Marsan, Eddie; Pardo, J. D.; Munteanu, Florian; Sutherland, Kiefer, 1966-; Hoss, Nina; et al. (Paramount, 2022)
Involuntarily discharged from the Army, a Special Forces sergeant lands a contract with a private underground military force. When his very first assignment goes awry, the elite soldier finds himself hunted and on the run, caught in a dangerous conspiracy and fighting to stay alive long enough to get home and uncover the true motives of those who betrayed him.
A U.S. special forces sergeant, who is involuntarily discharged from the Army and cut-off from his pension, joins an underground military organization in order to provide for his family, but soon finds himself hunted and on the run.
Originally released as a motion picture in 2022.
Director of photography, Pierre Aïm ; editor, Theis Schmidt ; music, Alex Belcher.
Chris Pine, Ben Foster, Gillian Jacobs, Eddie Marsan, JD Pardo, Kiefer Sutherland, Florian Munteanu, Nina Hoss, Amira Casar, Fares Fares.
MPA rating: R; for violence and language.
DVD, NTSC, region 1; wide screen; 5.1 Dolby digital, described video.
English dialogue; English or Spanish subtitles; closed-captioned; described video.
Keywords: Soldiers -- Drama; Mercenary troops -- Drama; Conspiracies -- Drama; Betrayal -- Drama; Feature films; Fiction films; Thrillers (Motion pictures); Action and adventure films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities